Formula of The Adultery Offense In The New National Criminal Code (Law Number 1 of 2023) To Juvenile Perpetrator: Would It Make The Juvenile Criminal Justice System Getting Aggravate? - Dhumillah, Dewic Sri Ratnaning; Windiyastuti, Feny (Dinasti Research, 2024)
The criminalization of immoral acts through Law Number 1 of 2023 concerning the New Criminal Code (KUHP) is in the spotlight. According to article 411 of the New Criminal Code, every person who has sexual intercourse with someone who is not their husband or wife is punished for adultery, including those who are not married. The criminalization of perpetrators who are not in a sexual marriage will have the potential to ensnare underage teenagers who have had premarital relations. The 2017 Indonesian Demographic and Health Survey (SDKI) (conducted every 5 years) revealed that among women and men who had had premarital sexual relations, 59% of women and 74% of men were teenagers aged 15-19 years. The expansion of the formulation of the offense of adultery will certainly affect the juvenile criminal justice system (SPPA) considering that currently the implementation and regulation of SPPA is still weak and far from ideal. This research aims to outline how the possible influence of the formulation of the regulation of the crime of adultery or overspill according to the new Criminal Code could greatly influence the juvenile criminal justice system in Indonesia. Using normative juridical methods and a